POLA ASUH ORANG TUA DALAM MENDIDIK ANAK USIA 4-7 TAHUN TENTANG BUDAYA BUGIS (MAPPATABE’) DI kota MAKASSAR - Syarif Nana; Rudi Amir; Yolandika Arsyad; Nur Alamsyah; Febriansa Febriansa (JAPPA: Jurnal Andragogi Pedagogi dan Pemberdayaan Masyarakat, 2026)
This study aims to the implementation of parenting patterns in educating children about bugis culture, Mappatabe in Makassar city, which consists of preliminary activities, core research and pentup, this research uses a qualitative approach with the type of research on parenting patterns in educating children about bugis culture mappatabe. This subject is from parents and children in Makassar city, this collection is done by observation interview method. The techniques used in data analysis are data reduction, data presentation and conclusion drawing.